Association of cropping practices, cropping areas, and foliar diseases of common bean (Phaseolus vulgaris L.) in Ethiopia - Tizazu Degu; Tesfaye Alemu; Asnake Desalegn; Berhanu Amsalu; Alemayehu Assefa (Journal of Agriculture and Food Research, 2023)
Common bean production is being constrained by a number of diseases. The survey was carried out to prioritize common bean diseases and their associations with cropping areas and cultural practices. A stratified random assessment on 114 farmer's fields was conducted in Ethiopia's four common bean producing zones (Metekel, Sidama, Wolaita, and Halaba). Data are collected randomly on disease severity, incidence levels, and agronomic practices. The results revealed that eleven foliar diseases were found to affect common bean production. Among them, the maximum disease severity and distribution was scored for angular leaf spot (Pseudocercospora griseola) (mean disease severity of 17.8%) and bean anthracnose (Colletotrichum lindemuthianum) (10.9%) followed by floury leaf spot (Mycovellosiella phaseoli), ascochyta blight (Ascochyta phaseolorum Sacc), and web blight (Thanatephorus cucumeris). A multiple correspondence analysis was conducted, and revealed a significant association between the diseases, cropping areas and cultural practices. Optimal crop density was found to be associated with lower bean anthracnose and mosaic virus severities, while being liked to high levels of angular leaf spot and frog-eye leaf spot. Additionally, optimum sowing dates were associated with low severities of bean anthracnose, angular leaf spot, frog-eye leaf spot, Halo Blight, and mosaic virus. On the other hand, a high weediness level was found to be associated with higher levels of web blight and bean anthracnose. Intercropping and row planting were obtained to reduce angular leaf spot and increase occurance of ascochyta blight compared to monocropping. Furthermore, row planting were found to decrease bean anthracnose, angular leaf spot, and cercospora leaf spot when compared to broadcasting. The application of fertilizer was found to decrease the occurances of bean anthracnose, halo blight, floury leaf spot, and angular leaf spot. Therefore, efforts should focus on the optimization and integration of cultural practices for managing disease and producing common bean sustainably.